Culture Differences and Challenges in Localization of Senior Executives of International Luxury Hotels in China. Issue 2 (2nd April 2016) - Chan, David; Ye, Tian; Xu, Honggang
ABSTRACT: With the rapid increase of international hotels in China, the importance of talent localization has widely been recognized, although empirical research is still limited. This paper explores the current situation of talent localization of international luxury hotels in China and its influencing factors from a cultural perspective through in-depth interviews with executives and senior managers of hotel associations, luxury hotels, and hotel owners. The findings indicate that the localization process of senior managers is still slow. One of the important barriers to the localization process is cultural differences, which are analyzed at the social, organizational, and individual levels. Contradictory pressures between standardization and localization and mistrust issues influenced by culture differences are further discussed. Practical implications are indicated.